Analisis Terhadap Penafsiran Imam Al-Alusy tentang Jin, Iblis, dan Setan - Nuramin Nuramin (UIN Sunan Gunung Djati Bandung, 2021)
Jinn, devils, and demons are creatures of God who are invisible or unseen. Allah created them as a sign that apart from humans, supernatural beings surround them and watch their movements from any direction they want. The three magical beings are believed to exist by all humanity. Belief in supernatural beings is an identity of faith that Muslims must possess; even Allah has confirmed it that among the characteristics of people who fear Allah are faith in the unseen, as stated in the letter Al-Baqarah verse 3, which reads: